P82 Treatment patterns in patients with stage IIIB-IV NSCLC in clinical practice: retrospective analysis of a UK trust database. (December 2018) - Snee, M; Cheeseman, S; Thompson, M; Lacoin, L; Sopwith, W; Godden, P; Chaib, C; Daumont, M; Penrod, JR; O'Donnell, J; Hall, G
Abstract : Background: I-O Optimise is a new multinational data platform developed to enable real-world insights into the management of thoracic malignancies. As part of this initiative, the current analysis reports the characteristics and treatment patterns for adult patients diagnosed with stage IIIB or IV NSCLC at one of the largest integrated cancer centres in the UK. Methods: Retrospective cohort study using longitudinal data already collected from electronic medical records, including all adult patients diagnosed with stage IIIB-IV NSCLC between January 2007 and August 2017. Minimum follow-up was 6 months. Distinct lines of therapy (LoT) were identified using a clinically-verified algorithm based on the name and date of systemic anti-cancer therapy (SACT) administered and the gap between two treatments. Results: Overall, 2119 patients were included. Mean age at diagnosis was 71.4±11.2 years. Nearly one-third (32.7%) were clinically diagnosed without pathological confirmation (table 1) and very few of these patients have SACT administration recorded. Following diagnosis, 648 patients (30.6%) received ≥1 LoT, 223 (10.5%)≥2 LoT and 60 (2.8%)≥3 LoT. Proportions of patients treated decreased with age (73.5% [25/34] aged 18–44 years; 52.7% [267/507] aged 45–64 years; 29.8% [310/1040] aged 65–79 years; 8.6% [46/538] aged 80+years) and performance score (58.5% [387/662] PS0–1; 38.2% [158/414] PS2; 6.1% [52/848] PS3–4). Between the periods 2007–2011 and 2012–2017, increased proportions were treated (28.2% [263/933] and 32.5% [385/1186] respectively). Patient characteristics of the treated cohort and regimens administered for 1st and 2nd LoT are shown (table 1). Conclusions: Around 70% of this real-world cohort did not receive any SACT, and the administration of treatment was strongly associated with age and performance status. The changing availability of treatment options over time (including the emergence of immunotherapy) and survival outcomes by LoT will be presented in more detail for the cohort described.